Family and community engagement in charter schools - Beabout, Brian R. (Family, school, community, partnership issues., 2024)
This edited volume is part of the Information Age Publishing (IAP) Series on Family, School and Community Partnerships. This book addresses the ways families and communities engage with an increasingly common feature of the American public education landscape: charter schools. Family and Community Engagement in Charter Schools contains seven chapters examining this emerging field of study authored by both established and emerging scholars. Chapters examine how charter schools, the policy landscape, families, community institutions, and charter school educators both create and inhibit opportunities for effective family and community engagement. Data is included from intensely charterized school districts such as Los Angeles, Denver, New York City, New Orleans and Oakland as well as broader state-level perspectives from California and Massachusetts. The authors approach this important relationship without the fixed ideological lens that often colors research on this controversial from of school organization.In addition to highlighting their unique findings, chapters propose practical, research-based strategies for schools, districts, or communities so that charter schools can be strong sources of local democracy- an oft-cited but rarely achieved goal. The book will broaden the field of Family and Community Engagement by including new theories, scholars, and areas of study. It is valuable reading for researchers, graduate students, policymakers, educational leaders, and community-based organizations seeking to better understand this unique form of organizing public schools.